Cost-effective diagnosis of male oxidative stress using the nitroblue tetrazolium test: useful application for the developing world - Amarasekara, D. S.; Wijerathna, S.; Fernando, C.; Udagama, P. V. (Andrologia, 2012)
Seminal oxidative stress plays an important role in male factor infertility (MFI), worldwide. A study was thus undertaken for the ﬁrst time to establish seminal reactive oxygen species (ROS) as a clinical marker of MFI in a cohort of Sri Lankan males. The nitro blue tetrazolium (NBT) assay for ROS estimation and modiﬁed Endtz test for detecting leucocytes were carried out on semen samples (N = 102) of sub-fertile males. Age-matched individuals (N = 30) with proven past paternity served as controls. Signiﬁcantly higher ROS production was evident in individuals with asthenozoospermia and unexplained infertility (Mann–Whitney U-test, P = 0.000), than of the fertile and the other sub-fertile groups tested. Receiver operating characteristic plot analysis established cut-off points of 40.57 and 42.02 lg formazan/107 spermatozoa for ROS to distinguish fertile males from asthenozoospermics (71.4% sensitivity: 70% speciﬁcity; AUC = 0.82), and from unexplained infertile males (74.1 % sensitivity: 73.3% speciﬁcity; AUC = 0.85) respectively. As ROS appear to be a potential marker of male infertility, it is imperative to validate this test as a simple, cost-effective hence a widely accessible diagnostic tool to be included in MFI investigations in the developing world
Keywords: Asthenozoospermia; reactive oxygen species; unexplained infertility; male factor infertility; oxidative stress